MODEL PENGEMBANGAN KOMPETENSI GURU MELALUI PELATIHAN DALAM JABATAN (Studi Pada Sekolah Menengah Atas Negeri Kota Pekanbaru Riau) - Adolf Bastian (Lectura : Jurnal Pendidikan, 2014)
Abstract: The aim of this research is to design a development model of teachers’competency through in-service training that can be used as a reference in designing,implementing and evaluating training activities in-service training at Public Senior HighSchool teachers. This research is a preliminary study of a research and development thatresults hypothetic model of teachers’ competency development through in-service trainingand stated 77 teachers as sample by using cluster random sampling. The data weregathered by using a set of questionnaires, interview, and check lists and then analyzed byusing percentage and then described.